A quantum inspired PSO algorithm for energy efficient clustering in wireless sensor networks. Issue 1 (1st January 2018) - Kanchan, Pradeep; Pushparaj, Shetty D
Abstract: Clustering is done in wireless sensor networks (WSN) to conserve the energy of sensor nodes in the network. Decreasing the energy consumption of nodes prolongs the lifetime of the WSN. A quantum bit can exist in "0" state, "1" state or a linear superposition of "0" and "1" states, unlike the binary bit which can exist in only "0" state or "1" state. In this paper, we propose a Quantum inspired PSO (particle swarm optimization) called Quantum-inspired PSO for Energy Efficient Clustering (QPSOEEC). The algorithm is tested by giving different values to the number of sensor nodes and cluster heads, varying the base station position, etc. Then, our results are compared to existing algorithms that demonstrate the superiority of our algorithm.